Drivers and barriers for learning within full-scale emergency response exercises. (18th August 2021) - Humann, Michael; Collie, Craig; Kisan, Virad; Crook, Phil
With increased demands on emergency response agencies and organisations, it essential that skills and capabilities are maintained during times of non-deployment. A unique setting to do this is during multi-agency full-scale exercises (FSX), which bring together partners and organisations who would be expected to cooperate and work together during emergency response deployments. During the delivery of a recent FSX - designed to establish a learning environment for players to practise disaster event response plans, policies and procedures - we reviewed the experience and perceptions of those who participated. Focusing on drivers and barriers for learning, we outline key factors that increase the benefit these have on individuals while also outlining components of exercises that can have a negative impact if not addressed correctly. We also provide recommendations for planning and delivery, aimed at increasing the return on investment when organising these events.